Composition and Activity of Microbial Communities along the Redox Gradient of an Alkaline, Hypersaline, Lake - Edwardson, Christian F.; Hollibaugh, James T. (Frontiers in Microbiology, 2018)
We compared the composition of microbial communities obtained by sequencing 16S rRNA amplicons with taxonomy derived from metatranscriptomes from the same samples. Samples were collected from alkaline, hypersaline Mono Lake, California, USA at five depths that captured the major redox zones of the lake during the onset of meromixis. The prokaryotic community was dominated by bacteria from the phyla Proteobacteria, Firmicutes, and Bacteroidetes, while the picoeukaryotic chlorophyte Picocystis dominated the eukaryotes. Most (80%) of the abundant (>1% relative abundance) OTUs recovered as amplicons of 16S rRNA genes have been reported in previous surveys, indicating that Mono Lake's microbial community has remained stable over 12 years that have included periods of regular, annual overturn interspersed by episodes of prolonged meromixis that result in extremely reducing conditions in bottom water. Metatranscriptomic sequences binned predominately to the Gammaproteobacteria genera Thioalkalivibrio (4-13%) and Thioalkalimicrobium (0-14%); and to the Firmicutes genera Dethiobacter (0-5%) and Clostridium (1-4%), which were also abundant in the 16S rRNA gene amplicon libraries. This study provides insight into the taxonomic affiliations of transcriptionally active communities of the lake’s water column under different redox conditions.